Psychosocial interventions for people with both severe mental illness and substance misuse - Hunt, Glenn E (Cochrane Database Syst Rev, 2019)
BACKGROUND: Even low levels of substance misuse by people with a severe mental illness can have detrimental effects. OBJECTIVES: To assess the effects of psychosocial interventions for reduction in substance use in people with a serious mental illness compared with standard care. SEARCH METHODS: The Information Specialist of the Cochrane Schizophrenia Group (CSG) searched the CSG Trials Register (2 May 2018), which is based on regular searches of major medical and scientific databases. SELECTION CRITERIA: We included all randomised controlled trials (RCTs) comparing psychosocial interventions for substance misuse with standard care in people with serious mental illness. DATA COLLECTION AND ANALYSIS: Review authors independently selected studies, extracted data and appraised study quality. For binary outcomes, we calculated standard estimates of risk ratio (RR) and their 95% confidence intervals (CIs) on an intention‐to‐treat basis. For continuous outcomes, we calculated the mean difference (MD) between groups. Where meta‐analyses were possible, we pooled data using a random‐effects model. Using the GRADE approach, we identified seven patient‐centred outcomes and assessed the quality of evidence for these within each comparison. MAIN RESULTS: Our review now includes 41 trials with a total of 4024 participants. We have identified nine comparisons within the included trials and present a summary of our main findings for seven of these below. We were unable to summarise many findings due to skewed data or because trials did not measure the outcome of interest. In general, evidence was rated as low‐ or very‐low quality due to high or unclear risks of bias because of poor trial methods, or inadequately reported methods, and imprecision due to small sample sizes, low event rates and wide confidence intervals. 1. Integrated models of care versus standard care (36 months) No clear differences were found between treatment groups for loss to treatment (RR 1.09, 95% CI 0.82 to 1.45; participants = 603; studies = 3; low‐quality evidence), death (RR 1.18, 95% CI 0.39 to 3.57; participants = 421; studies = 2; low‐quality evidence), alcohol use (RR 1.15, 95% CI 0.84 to 1.56; participants = 143; studies = 1; low‐quality evidence), substance use (drug) (RR 0.89, 95% CI 0.63 to 1.25; participants = 85; studies = 1; low‐quality evidence), global assessment of functioning (GAF) scores (MD 0.40, 95% CI ‐2.47 to 3.27; participants = 170; studies = 1; low‐quality evidence), or general life satisfaction (QOLI) scores (MD 0.10, 95% CI ‐0.18 to 0.38; participants = 373; studies = 2; moderate‐quality evidence). 2. Non‐integrated models of care versus standard care There was no clear difference between treatment groups for numbers lost to treatment at 12 months (RR 1.21, 95% CI 0.73 to 1.99; participants = 134; studies = 3; very low‐quality evidence). 3. Cognitive behavioural therapy (CBT) versus standard care There was no clear difference between treatment groups for numbers lost to treatment at three months (RR 1.12, 95% CI 0.44 to 2.86; participants = 152; studies = 2; low‐quality evidence), cannabis use at six months (RR 1.30, 95% CI 0.79 to 2.15; participants = 47; studies = 1; very low‐quality evidence) or mental state insight (IS) scores by three months (MD 0.52, 95% CI ‐0.78 to 1.82; participants = 105; studies = 1; low‐quality evidence). 4. Contingency management versus standard care We found no clear differences between treatment groups for numbers lost to treatment at three months (RR 1.55, 95% CI 1.13 to 2.11; participants = 255; studies = 2; moderate‐quality evidence), number of stimulant positive urine tests at six months (RR 0.83, 95% CI 0.65 to 1.06; participants = 176; studies = 1) or hospitalisations (RR 0.21, 95% CI 0.05 to 0.93; participants = 176; studies = 1); both low‐quality evidence. 5. Motivational interviewing (MI) versus standard care We found no clear differences between treatment groups for numbers lost to treatment at six months (RR 1.71, 95% CI 0.63 to 4.64; participants = 62; studies = 1). A clear difference, favouring MI, was observed for abstaining from alcohol (RR 0.36, 95% CI 0.17 to 0.75; participants = 28; studies = 1) but not other substances (MD ‐0.07, 95% CI ‐0.56 to 0.42; participants = 89; studies = 1), and no differences were observed in mental state general severity (SCL‐90‐R) scores (MD ‐0.19, 95% CI ‐0.59 to 0.21; participants = 30; studies = 1). All very low‐quality evidence. 6. Skills training versus standard care At 12 months, there were no clear differences between treatment groups for numbers lost to treatment (RR 1.42, 95% CI 0.20 to 10.10; participants = 122; studies = 3) or death (RR 0.15, 95% CI 0.02 to 1.42; participants = 121; studies = 1). Very low‐quality, and low‐quality evidence, respectively. 7. CBT + MI versus standard care At 12 months, there was no clear difference between treatment groups for numbers lost to treatment (RR 0.99, 95% CI 0.62 to 1.59; participants = 327; studies = 1; low‐quality evidence), number of deaths (RR 0.60, 95% CI 0.20 to 1.76; participants = 603; studies = 4; low‐quality evidence), relapse (RR 0.50, 95% CI 0.24 to 1.04; participants = 36; studies = 1; very low‐quality evidence), or GAF scores (MD 1.24, 95% CI ‐1.86 to 4.34; participants = 445; studies = 4; very low‐quality evidence). There was also no clear difference in reduction of drug use by six months (MD 0.19, 95% CI ‐0.22 to 0.60; participants = 119; studies = 1; low‐quality evidence). AUTHORS' CONCLUSIONS: We included 41 RCTs but were unable to use much data for analyses. There is currently no high‐quality evidence to support any one psychosocial treatment over standard care for important outcomes such as remaining in treatment, reduction in substance use or improving mental or global state in people with serious mental illnesses and substance misuse. Furthermore, methodological difficulties exist which hinder pooling and interpreting results. Further high‐quality trials are required which address these concerns and improve the evidence in this important area.